Pengaruh Fraud Hexagon terhadap Kecurangan Laporan Keuangan : (Studi Empiris pada Perusahaan Sektor Healthcare yang Terdaftar pada Bursa Efek Indonesia Periode 2019-2023) - Dwi Sukmajati; Prita Andini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine and analyze the effect of fraud hexagon to fraudulent financial statements. Fraud hexagon consists of pressure is proxied by financial stability, opportunity is proxied by ineffective monitoring, rationalization is proxied by change of auditor, capability is proxied by change of director, arrogance is proxied by frequent number of ceo’s picture and collusion is proxied by government projects. This study uses a sample of healthcare sector companies listed in Indonesia Stock Exchange (IDX) during the 2019- 2023 period with a total sample of 18 companies and uses a purposive sampling technique. The analytical tool used in this study is logistic regression. The results of this study indicate that change of director and government projects has a negative effect on the financial statement fraud, while financial stability, ineffective monitoring, change of auditor and frequent number of ceo’s picture do not effect the financial statement fraud.